A RARE CASE OF OSTEOID OSTEOMA IN MANDIBLE MIMICKING A PERIAPICAL INFLAMATORY LESION-case report - Kacarska, Marina (Journal of Morphological Sciences; Vol 4 No 2 (2021): JMS, 2021)
Osteoid osteoma is an uncommon non odontogenic benign bone neoplasm that rarely occurs in the jaw bones. This article presents a rare case of osteoid osteoma in mandible mimicking a periapical inflammatory lesion. The patient reported without symptoms and in good general health. Intraorally, there was a swelling in the periapical region of the left mandibular first bicuspid. Vitality test was negative. Orthopantomography depicted a well defined unilocular periapical radiolucency incasing the apical third of the mandibular first bicuspid, with osteosclerotic rim on its distal prospect. Such clinical findings were appropriate for chronic periapical inflammatory lesion, so periapical surgery was scheduled. During surgery, apicoectomy was performed, the lesion removed and sent for histopathology. The result showed irregularly proliferated trabeculae with disrupted architecture and visible osteoid accumulations typical for osteoid osteoma. Periodic follow ups were scheduled.  No recurrence was noted. Although rare, osteoid osteoma in mandible can mimic a periapical inflammatory lesion. Surgical removal and histology contributed to proper diagnostics. Complete surgical removal prevented recurrence. Keywords : osteoid osteoma, mandible, periapical inflammatory lesion, surgery, nonvital bicuspid, histology https://doi.org/10.55302/JMS2142129k